Heterotopic Pancreas in the Gallbladder: Case Report and Literature Review - Emad Aborajooh; Ibrahim Khalil Khairi Ghayada; Yasser Mustafa Issa Lafi (Case Reports in Medicine)
Introduction. Heterotopic pancreas (HP) is the congenital presence of pancreatic tissue outside its normal location in the absence of vascular and anatomical connection with the main pancreas. HP can affect any part of the gastrointestinal tract, and it is mostly encountered in the stomach. The gallbladder is a rare site of HP, and our literature review revealed that only 38 cases were reported. We present a case of HP in the gallbladder that was presented with a picture of acute cholecystitis. After the case presentation, we will discuss HP in the gallbladder by reviewing the literature. Case Presentation. A 49-year-old male presented to the emergency department complaining of progressively worsening right upper abdominal pain for the last 24 hours. After thorough history and physical examination, a provisional diagnosis of acute cholecystitis was made. Abdominal ultrasonography revealed a rim of edema surrounding the gallbladder wall with two stones impacted at the gallbladder neck. Laparoscopic cholecystectomy was performed with an uneventful postoperative course, and the patient was discharged the next day. Microscopic examination of the gallbladder showed that a heterotopic pancreatic tissue, composed of a large number of pancreatic acini and few ducts with the absence of islets of Langerhans, was found around the cystic duct. The patient was asymptomatic at the regular follow-up six months postoperatively. Conclusion. HP in the gallbladder is an extremely rare finding. Its clinical presentation is not different from other cholecystopathic diseases. Most cases were accompanied by cholelithiasis. Preoperative laboratory and imaging modalities are usually not helpful in the diagnosis of HP in the gallbladder. The definitive diagnosis is made by histological examination of the gallbladder specimen. Laparoscopic cholecystectomy is sufficing treatment.